Implementasi Nilai-Nilai Islam Tentang Pelestarian Alam Dalam Pengembangan Bahan Ajar Pendidikan Agama Islam di Madrasah Tsanawiyah Al-Khoirot - Vina Lailatul Maskuro; Muhammad Husni (Jurnal Al-Fatih, 2026)
This study aims to analyze the implementation of Islamic values ??on environmental conservation into Islamic Religious Education (PAI) teaching materials at MTs Al-Khoirot Putri Malang in order to trigger students' critical-ecological awareness of the SDGs. Using the ADDIE Research and Development (R&D) method integrated with a descriptive-qualitative approach, through interviews, observations, and document analysis. The development results show that the integration of ecological theology into eco-project-based modules is very effective. The general results and summary of the main results prove an increase in real concern; of the 21 female students who were less environmentally aware, 16 of them actively transformed to maintain sanitation and reduce plastic waste. In conclusion, the contextualization of Islamic theology in madrasas has successfully formed environmentally friendly behavior. The main contribution of this study is to provide a transformative curriculum model that bridges the doctrine of hygiene with modern environmental science.